Sensor Ultrasonic dan Servo Motor untuk Selection Belt Conveyor Prototype Berbasis Arduino - Adhie Tri Wahyudi; Bagus Ismail Adhi Wicaksana (Program Studi Teknik Industri Universitas Setia Budi, 2019)
The purpose of this article publication is to present a prototype of selection belt conveyor design. Requirement specification which is the basis of design is a conveyor equipped with an object height detection device and a selection based on object height. This research was carried out with the sketch design stages using SketchUp software, planning the wiring scheme with the help of the Fritzing software, designing the Arduino microcontroller program code, assembling the conveyor belt and functional testing. The results of trials conducted with three repetitions showed that the prototype was operational as expected specification specifications. The prototype is able to detect objects moving through the ultrasonic sensor, then the servo motor's hand is able to make selections of objects whose height corresponds. Three output basket boxes contain three objects of the same selection.